(untitled) (Damascus University Journal of arts and humanities sciences, 2023)
In this article, an attempt is made to monitor the introduction of proverbs and the popular ideas and events that took place in their course. In the fabric of the poetic texts of the Abbasid poet Muslim bin Al-Walid. The importance of this research comes from the fact that it is an attempt to read the ancient text with a mechanism that is considered a tributary that flows into the stream of modern linguistic criticism that tries to break the barriers between language and literature: which are the sources of meanings or what has become known in modern criticism as the mechanism of intertextuality, through the fact that the research pays great attention to the applied side. And tries to benefit from the various data in order to reach the true significance of the texts